Fire Risk Assessment and Evaluation of the Effectiveness of Fire Protection Actions in a Combined-Cycle Power Plant - Taleb Askaripoor; Elaheh Kazemi; Mostafa Marzban (Iranian Journal of Health, Safety and Environment, 2020)
The increasing abundance of fires in industrial buildings has led to the growth of fire risk assessment and protection methods. However, few studies have been performed on the practical application of these risk assessment methods in industrial structures. This study aimed at assessing fire risk and determining the effectiveness of fire control measures to reduce fire-related injuries and fatalities to occupants at a combined-cycle power plant in the northeast of Iran. In the present study, firstly, the fire risk level of the real condition for the occupants, building and contents, and activities were measured using the Fire Risk Assessment Method for Engineering (FRAME). Then, taking into account the fire control measures, the fire risk was recalculated and compared with the acceptable risk level. The results indicated that the occupants' fire risk level was 1.26 that was above the acceptable level. Furthermore, in the case of a fire, the expected destruction of the control room will be approximately 20%. Assuming a constant fire load modulation via building construction by non-burning materials or up to 10% burning materials, the occupants' fire risk level will be decreased by 8% compared to the current situation. Also, in the state of designing standard emergency exit routes and using the fire alarm system, the fire risk level will be decreased by 50% and 52%, respectively, compared to the current condition. This study indicated that applying quantitative engineering methods for fire risk assessment can help to find practical solutions to minimize losses and fire-related injuries to industrial building occupants.